Simultaneous Enhancement of Magnetothermal and Photothermal Responses by Zn, Co Co‐Doped Ferrite Nanoparticles. Issue 52 (6th November 2022) - Yu, Xiang; Yang, Tianyu; Liu, Ruoshui; Wu, Di'an; Tian, Daming; Zhou, Tianshi; Yan, Haitao; He, Shuli; Zeng, Hao
Abstract: Reducing nanoparticle (NP) dosage for hyperthermia therapy has remained a great challenge. In this work, efficiencies of alternating current (AC) magnetic field and near‐infrared (NIR) heating are simultaneously enhanced by Zn and Co co‐doping of magnetite NPs. The optimum magnetic anisotropy for maximized loss power under each magnetic field is achieved by tuning the doping concentration. The specific loss power of Zn0.3 Co0.08 Fe2.62 O4 @SiO2 NPs reaches 2428 W g −1 under an AC field of 27 kA m −1 at 430 kHz; 12 296 W g −1 under NIR laser irradiation at 808 nm and 2.5 W cm −2 ; and an unprecedented value of 14 724 W g −1 under dual mode. These values far exceed what has been achieved previously in iron oxide NPs. Ex vivo experiments on sacrificial mice show that while the NP dosage is substantially reduced to that used for magnetic resonance imaging, the surface body temperature of the mice reaches 50 °C after exposure to both AC field and laser irradiation under field parameters and laser intensity below safety limits. This nanoplatform is thus promising for multi‐modal local hyperthermia therapy. Abstract : Efficiencies of alternating current (AC) magnetic field and near‐infrared (NIR) heating are simultaneously enhanced by Zn and Co co‐doping of magnetite nanoparticles (NPs). These bio‐compatible NP heating agents with exceptionally high specific loss power (SLP) achieve record SLP for hyperthermia applications below the biological safety limitation including both AC field exposure and laser irradiation.